Dynamic Output‐Feedback Control for T‐S Fuzzy Systems with Input Time‐Varying Delay. Issue 6 (8th April 2016) - Zhang, Ziye; Lin, Chong; Chen, Bing
Abstract: This paper considers the problem of the H ∞ control for T‐S fuzzy systems with input time‐varying delay via dynamic output feedback. Firstly, by applying the reciprocally convex approach, new delay‐dependent sufficient condition for H ∞ performance analysis is obtained. Then, a less conservative condition for the existence of the H ∞ controllers is given in terms of linear matrix inequalities (LMIs). Moreover, in the considered system, the time‐delay term is included in the measured output. This results in the difficulty in designing the controllers being increased and the obtained results being applied to a wider class of fuzzy systems than the most existing ones. The main contribution of this work lies in the application of the reciprocally convex inequality and the time‐delay term included in the measured output. Finally, the advantages and effectiveness of the present results are shown by several numerical examples.